Role of Follicular Size on Oocyte Recovery Rate and in Vitro Embryo Production Stages in Local Iraqi Sheep - Mustafa Ghassan Sulaiman; Abdul Sattar Faraj. (مجلة الانبار للعلوم البيطرية)
In vitro embryo production (IVEP) encompasses a series of three basic steps, namely in vitro maturation (IVM), in vitro fertilisation (IVF), and in vitro embryo culture. IVEP approach has shown to be a valuable tool in advancing our comprehension of early mammalian development and expediting genetic enhancement in livestock. The aim of this research was to compare the impact of small and large follicles on the total number of oocytes recovered through the IVEP process. Therefore, 305 Ewe genitalia were collected at the Al-Fallujah abattoir in the Al-Anbar province. The follicles were identified, and their diameter was measured using an automated vernier calliper. Subsequently, the oocytes were classified into three distinct groups, namely excellent (A), acceptable (B), and poor (C). The results of the maturation rate of large follicles were 43.9% (51/116) and small follicles 30.7% (20/65). There was a statistical difference in maturation rate (p<0.05). The fertilization rate of matured oocytes collected from large follicles was 60.7% (31/51) and 50% (10/20) from small follicles. There was no statistical difference. The results of Blastocyst production rate. showed a higher percentage 58.06 (18/31) of Blastocyst produced from large follicles as compared a percentage of 30% (3/10) of Blastocyst production from small follicles. There was a statistical difference (P<0.05). It was concluded from the current study that the size of the follicle has an effect on IVM, IVF and IVC.